Digital applications and games in school literacy process - Lemos, Adriana Falqueto; Vilela, Janaína Franciele do Couto; Couto, Tiele Pereira do (Revista Letras Raras, 2023)
This study deals with the use of existing educational digital apps and games that were designed to be worked on in the literacy process, with regard to BNCC-related skills. The objective is to investigate how these digital technological tools can help teachers in the literacy process of students in a playful way. For this, a bibliographic research with a qualitative approach was used, - with methodology support by Lemos (2020), based on the literature review on the research topic and the analysis of four games, Aprenda ler a escrever - Aprenda o alfabeto, Graphogame, Forma palavra and Palavra secreta. As a result, it can be said that the use of various applications and digital games is of great importance to help the teacher, since it generates appropriate pedagogical resources with the capacity to expand the forms of teaching and learning in an innovative way, increasing motivation, interaction, attention, positively stimulating students’ reading and writing in the literacy process.